2001
DOI: 10.1139/cjz-79-2-325
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioural responses of female mountain white-crowned sparrows to natal- and foreign-dialect songs

Abstract: The objective of this study was to determine the effect of early song learning on physiological and behavioural responses to song in adulthood in female mountain white-crowned sparrows (Zonotrichia leucophrys oriantha). Juvenile females were captured before they had dispersed from their natal region. In experiment 1, natal-dialect song, foreign-dialect song, and heterospecific song were played back to the birds during photostimulation when they were 1 year old and physiological responses were measured. The phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Our results are also consistent with data recently obtained by MacDougall-Shackleton et al (2001). They studied the effect of early song learning on behavioural responses to song in adulthood in female mountain white-crowned sparrows (Zonotrichia leucophrys oriantha).…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Our results are also consistent with data recently obtained by MacDougall-Shackleton et al (2001). They studied the effect of early song learning on behavioural responses to song in adulthood in female mountain white-crowned sparrows (Zonotrichia leucophrys oriantha).…”
Section: Discussionsupporting
confidence: 95%
“…The birds showed a clear preference for nataldialect song, exhibiting more displays to natal-dialect song than to foreign-dialect or heterospecific song. However, the authors found that this effect was attenuated in birds that had heard heterospecific or foreign-dialect song when they were 1 year old (MacDougall-Shackleton et al 2001). The authors suggested that the song playback during the late exposure would correspond to a female sparrow's first breeding season.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…For instance, female white-crowned sparrows (Zonotrichia leucophrys) normally prefer their natal song dialect. However, if they experience a more prevalent foreign dialect during preceding months, females exhibit no choice-bias toward either song type (MacDougall-Shackleton et al 2001). This suggests that when the prevailing song environment is lacking in the preferred song type, females adjust the threshold for choosing a male as a mate.…”
Section: Modulation Of Mate-choice Decisions By the Song Environmentmentioning
confidence: 95%